RENDEMEN, AROMA, RASA, PENAMPILAN KEJU LUNAK DARI SUSU SAPI DENGAN PENAMBAHAN RENNET DAN STARTER BAL YOGHURT BIOKUL - Rizki Adrianto; Damar Wiraputra; Masmulki Daniro Jyoti; Arifia Zulaika Andaningrum (Jurnal Agritechno, 2020)
Cheese is a product of milk, mostly imported from other countries. Therefore it is very important to develop using locally available materials. This study was conducted to compare the effects of a given treatment. Soft cheese composition made from cow's milk using direct pickling techniques. This research used fresh cow's milk from Lampung State Polytechnic, LAB starter from “biokul” brand and rennet as a coagulant. The treatment consisted of 2 treatments, namely making cheese with the addition of rennet and adding rennet + starter LAB. The variables measured were yield, aroma, taste, and overall appearance. The results showed that the direct acidification technique using the LAB starter is feasible for use in the process of making soft cheese from cow's milk. The advantage of this technique is that it is fast, easy and cheap. The yield and composition of soft cheese from cow's milk varies depending on the treatment at the time of cheese making. To produce soft cheese with high yield, good aroma, taste, and overall appearance, it is recommended to use the rennet + starter LAB treatment.